Twinning-assisted dynamic adjustment of grain boundary mobility - Qishan Huang (Nature Portfolio, 2021)
Grain boundary can change its structure upon deformation. Here, the authors show that during this process, grain boundary mobility can be tuned dynamically via a self-stimulated twinning process.